Characterization of intestinal mononuclear phagocyte subsets in young ruminants at homeostasis and during Cryptosporidium parvum infection - Baillou, Ambre; Tomal, Florian; Chaumeil, Thierry; Barc, Céline; Levern, Yves; Sausset, Alix; Pezier, Tiffany; Schulthess, Julie; Peltier-Pain, Pauline; Laurent, Fabrice; Lacroix-Lamandé, Sonia (Frontiers in Immunology, 2024)
Introduction Cryptosporidiosis is a poorly controlled zoonosis caused by an intestinal parasite, Cryptosporidium parvum, with a high prevalence in livestock (cattle, sheep, and goats). Young animals are particularly susceptible to this infection due to the immaturity of their intestinal immune system. In a neonatal mouse model, we previously demonstrated the importance of the innate immunity and particularly of type 1 conventional dendritic cells (cDC1) among mononuclear phagocytes (MPs) in controlling the acute phase of C. parvum infection. These immune populations are well described in mice and humans, but their fine characterization in the intestine of young ruminants remained to be further explored. Methods Immune cells of the small intestinal Peyer’s patches and of the distal jejunum were isolated from naive lambs and calves at different ages. This was followed by their fine characterization by flow cytometry and transcriptomic analyses (q-RT-PCR and single cell RNAseq (lamb cells)). Newborn animals were infected with C. parvum, clinical signs and parasite burden were quantified, and isolated MP cells were characterized by flow cytometry in comparison with age matched control animals. Results Here, we identified one population of macrophages and three subsets of cDC (cDC1, cDC2, and a minor cDC subset with migratory properties) in the intestine of lamb and calf by phenotypic and targeted gene expression analyses. Unsupervised single-cell transcriptomic analysis confirmed the identification of these four intestinal MP subpopulations in lamb, while highlighting a deeper diversity of cell subsets among monocytic and dendritic cells. We demonstrated a weak proportion of cDC1 in the intestine of highly susceptible newborn lambs together with an increase of these cells within the first days of life and in response to the infection. Discussion Considering cDC1 importance for efficient parasite control in the mouse model, one may speculate that the cDC1/cDC2 ratio plays also a key role for the efficient control of C. parvum in young ruminants. In this study, we established the first fine characterization of intestinal MP subsets in young lambs and calves providing new insights for comparative immunology of the intestinal MP system across species and for future investigations on host–Cryptosporidium interactions in target species.